1998
DOI: 10.1088/0305-4470/31/15/007
|View full text |Cite
|
Sign up to set email alerts
|

Probabilistic analysis of the number partitioning problem

Abstract: Given a sequence of N positive real numbers {a 1 , a 2 , . . . , a N }, the number partitioning problem consists of partitioning them into two sets such that the absolute value of the difference of the sums of a j over the two sets is minimized. In the case that the a j 's are statistically independent random variables uniformly distributed in the unit interval, this NP-complete problem is equivalent to the problem of finding the ground state of an infinite-range, random anti-ferromagnetic Ising model. We empl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(66 citation statements)
references
References 21 publications
(38 reference statements)
4
62
0
Order By: Relevance
“…The barriers in equation (12), which are proportional to the logarithm of the energy, do not appear in any of the coarsening classes introduced by Lai et al [54]. The difference seems to be that here there are entropy barriers.…”
Section: Heuristic Arguments For Power Law Relaxationmentioning
confidence: 81%
See 1 more Smart Citation
“…The barriers in equation (12), which are proportional to the logarithm of the energy, do not appear in any of the coarsening classes introduced by Lai et al [54]. The difference seems to be that here there are entropy barriers.…”
Section: Heuristic Arguments For Power Law Relaxationmentioning
confidence: 81%
“…As an example, phase transitions in optimization problems have been discovered and studied using statistical mechanics [6,7]. Other problems studied using physical methods include the knapsack-problem [8], graph-partitioning [9], minimax-games [10], the 8-Queens problem [11], number partitioning [12,13] and the stable marriage problem [14]. Field theory has also been used to study, e.g., the enumeration of Hamiltonian cycles on graphs [15] and coloring of random, planar graphs [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Further studies within the physics community, have confirmed the existence of the NPP phase transition characterising it rigorously [17,18]. However, they provide no direct answer to the question of what features of the corresponding fitness landscapes, if any, are responsible for the widely different observed behaviour.…”
Section: The Number Partitioning Fitness Landscapementioning
confidence: 99%
“…According to [6] there is an expected exponential number of perfect partitions for κ < κc, and no expected perfect partition for κ > κc. We generated instances with several different sizes, ranging from sets A with ten elements (N = 10) to a thousand (N = 1000).…”
Section: Benchmark Instancesmentioning
confidence: 99%